The Tribe - Platform of participatory local development and management of communal rangeland resources - Nefzaoui A; Elmourid M; Louhaichi, Mounir (2014)
Sustainable development of pastoral and agro-pastoral systems, dominated by collective and/or tribal ownership of rangelands, is a key issue for the West Asia and North Africa region. These two systems are located in arid and semi-arid areas and are increasingly threatened by desertification process. The policy responses to tackle this complexity have been a sectorial and fragmented, “top-down” approach, putting forward technical solutions and neglecting the social context. In response to the frequent failures, methods of “participatory development” emerged during the 1970’s within international development arenas. Adoption of participatory approaches by national governments and its translation into actual implementation appears not only partial, but also particularly slow. Recent experiences suggest that integrated and participatory approaches may lead to more sustainable resource management and to more effective poverty oriented policies. Promotion of local/community development is the most recent approach to face the challenges of rangeland development. It aims at organizing people on a decentralized basis and applying participatory programming which could lead to effectively empowering the local people. In this context, the collaborative research program conducted by ICARDA and IFAD in Southern Tunisia has led to the development of tools and methods adapted to the development of collective desert rangeland ecosystems based on the empowerment of local rural poor communities and using innovative participatory approaches. The pilot action conducted showed that participatory natural resources management in such areas can be instrumental in institutionalizing participatory approaches. In both democratic and non-democratic settings, these approaches foster inclusiveness, transparency and accountability of public services and policy making processes. The tools developed play an essential educational role in changing bureaucrats and people’s mind-sets and communication patterns.